STUDI CELAH ENERGY 1,3,4 MONOMER DAN DIMER TIADIAZOL TERSUBSTITUSI-BH2 - Rahmi, Elvy (Sainstek : Jurnal Sains dan Teknologi, 2012)
The band gap of a 1,3,4 thiadiazole of monomer and dimmer in anti position, monomer and dimer of its ? BH2 substituted of those compounds had been studied by Calzaferri method. The optimized geometry had been obtained by optimizing the bond length (l) arA bond angel (?). The bond surface (?) was not been optimized since those molecules were assumed to be planar. The band gap was determined by measuring the different of HOMO and LUMO of the optimal condition. From there studies it were obtained that the Eg 1,3,4 thiadiazole monomer ard dimer in anti position, monomer and dimer of its substiruted - BH2 were 4,35793 eV; 3.31008eV ; 4.8900eV ;3,09322 eV; 3.11124 eV, respectively. Based on Eg. valued it was concluded that monomer substituted by -BH2, 1,3,4 thidiazole diamer in anti position and dimmer of its substituted - BH2 have Eg in semiconductor range (1,0-3,5 eV). The 1,3,4 thiadiazole monomer had Eg in the isolator range.Key words: Monomer, Dimer, Tiadiazol Tersubstitusi-BH2